Simulation of Nanofluid in L-shaped Cavities using COMSOL - Johilil@Jiran, Atirah Iffani; Kamardan, Muhammad Ghazali (Enhanced Knowledge in Sciences and Technology, 2023)
Simulation free convection flow of nanofluid in L-shaped cavities has been conducted in this study. The aim of this study is to simulate nanofluid flows in L-shaped cavities using a software, COMSOL Multiphysics. This case was chosen for use in COMSOL Multiphysics 6.0 to provide an appropriate guidance in solving mathematics modelling to demonstrate the impacts of the Rayleigh number, aspect ratio of the L-shaped cavity, and volume fraction of the Copper nanoparticles on the flow and thermal fields and heat transfer inside the cavity. The finite volume approach was applied, and it was discovered that decreasing the aspect ratio of the cavity postpones the transition from conduction to convection. Furthermore, it is discovered that the rate of heat transmission increases when the aspect ratio of the cavity decreases.